Daily temperature with non- accidental mortality in kedah and penang from 2011- 2019: a time series regression study - Sapari, Hadita (2024)
Extreme temperature is one of the major public health concerns due to significant health impacts to humans. Hence, understanding the distinct patterns of temperature-related mortality for each geographical area becomes essential as global temperatures rise. This study examined the association between daily ambient temperature and non-accidental mortality in Kedah and Penang. Daily data on meteorology, air pollutants, non- accidental, cardiovascular and respiratory mortality during 2011-2019 were obtained. A quasi-Poisson generalized linear regression with a distributed lag non-linear model (DLNM) was applied to estimate the temperature and mortality association. A non- linear U-shaped and J-shaped relationship between mean temperature and non- accidental mortality was observed for cumulative effects of 21 days for Kedah and Penang respectively. The minimum mortality temperature (MMT) at 27.4°C and 28.2°C were observed for Kedah and Penang respectively. Heat effects were significant for non-accidental and respiratory mortality. No significant relationship was found between all categories of mortality with lower temperature in both states. In Kedah, the relative risk associated with extremely high temperature compared to MMT was highest at lag 0-3 (RR: 1.16 (95% CI: 1.08, 1.26) for non-accidental mortality and lag 0-7 (RR: 1.23 (95% CI: 1.03, 1.49) for respiratory mortality. Meanwhile, Penang demonstrated the highest relative risk associated with extremely high temperature compared to MMT at lag 0-7 (RR: 1.21 (95% CI: 1.11, 1.33) for non-accidental mortality and lag 0-14 (RR: 1.57 (95% CI: 1.24, 1.99) for respiratory mortality. No significant risk for cardiovascular mortality was seen during extreme temperature exposure. Spatio- temporal mapping revealed a slight increase in mean temperature was observed during 2016-2019, as compared to 2011-2015, with more districts experienced hotter temperature. People with respiratory disease, the elderly, both genders, and those living in urban and rural pose a significant risk of mortality following exposure to extremely high temperatures. Air pollutants did not modify the temperature mortality relationship as no significant change in the temperature-mortality risk estimates was observed during sensitivity analysis. Our results urge the implementation of climate-resilient health policies, including urban planning, the development of Heat-Health Warning Systems (HHWSs), strengthening healthcare systems and preparedness, enhancing infrastructure resilience, and prioritizing vulnerable groups with community-specific strategies, particularly in high-risk areas. These insights guide policymakers and practitioners in addressing the complex interplay between climate and public health in Kedah and Penang.